The zoogeographic significance of Caraballo mountain range, Luzon island, Philippines with focus on the biogeography of Luzon's Herpetofauna - Gojo Cruz, Paul Henric P.; Afuang, Leticia E. (2018)
Our recent survey in the Caraballo Mountain Range contributed knowledge about the distribution of herpetofauna of Luzon Island, and allowed comparison of species composition among Luzon?s biogeographic regions. Data collection was done using intensive herpetofaunal survey in the sampling area in Pantabangan-Carranglan Watershed in Carranglan, Nueva Ecija in the Caraballo Mountains. Comparison with Luzon?s mountain ranges was done using presence-based Jaccard similarity index. Extensive literature survey of available distribution data for Luzons? herpetofauna revealed 153 native and non-native species (45 species of frogs, 65 lizards, 40 snakes, and 3 turtles) representing about 44% of the Philippine herpetofauna. Twenty-five (25) species of frogs and 71 species of reptiles are considered as restricted range, found only in one to three biogeographic regions. Jaccard similarity index showed that the herpetofauna of the Caraballo is most similar to that of the northern Sierra Madre (J= 0.50) and Cordillera Mountain Ranges (J=0.45). The available data showed that the Caraballo has a variable role with regards to Luzon?s herpetofaunal biogeography. The Caraballo possess frogs and snakes that are also found in the Sierra Madre and Cordillera, implying that the mountain range is a site of amalgamation for these faunas. On the other hand, it serves as a filter zone and dispersal barrier for burrowing and diminutive skinks and frugivorous varanids, based on the observed distribution of some members of the genus Brachymeles, Parvoscincus, and Varanus. This result confirms the importance of the Caraballo Range as an important biogeographic link between Sierra Madre and Cordilleras. This maybe attributed to the physical connection that provides shared topography and bioclimatic conditions among the biogeographic regions.